Antibacterial effect and biological reaction of calcium phosphate cement impregnated with iodine for use in bone defects. (May 2023) - Morinaga, Sei; Yamamoto, Norio; Tokoro, Masaharu; Hayashi, Katsuhiro; Takeuchi, Akihiko; Miwa, Shinji; Igarashi, Kentaro; Taniguchi, Yuta; Asano, Yohei; Nojima, Takayuki; Tsuchiya, Hiroyuki
Calcium phosphate cement (CPC) is often used to repair bone defects that occur after bone tumor and fracture treatment. To address bone defect cases with a high infection risk, developing CPCs with a longlasting wide-spectrum antibacterial effect is critical. Povidone-iodine has a wide antibacterial spectrum. Though there have been some reports of CPC containing antibiotics, no report of CPC with iodine has been described. In this study, the antibacterial effect and biological reaction of CPC impregnated with iodine was investigated. Iodine release from CPC and bone cement with various iodine contents (2.5, 5, and 20%) was evaluated, and 5 %-iodine CPC retained more iodine than the other CPCs after one week. Antibacterial activity against Staphylococcus aureus and Escherichia coli was also investigated, showing that 5 %-iodine had an antibacterial effect for up to eight weeks. Cytocompatibility was assessed, and 5 %-iodine CPC showed the same amount of fibroblast colony formation as control samples. CPCs with varying iodine contents (0, 5, and 20%) were then inserted into lateral femora of Japanese white rabbits for histological analysis. Osteoconductivity was evaluated using scanning electron microscopy, and hematoxylin-eosin staining. Consecutive bone formation was observed around all CPCs at eight weeks. These results indicate that CPC impregnated with iodine exhibits antimicrobial activity and cytocompatibility, and therefore, it may be effective for bone defect cases with high infection risk. Graphical Abstract